ANALISIS EFEKTIVITAS TRANSMISI KEBIJAKAN MONETER GANDA DI INDONESIA - Ingrit Magdalena; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2014)
This study aims to examine the monetary transmission of dual banking system from is a conventional and sharia to the inflation rate. In this study, the model used is the Vector Error correction model (VECM) and Granger Causality Test which aims to look at the relationship and linkages Dual transmission of monetary policy from the conventional and sharia policy against inflation. The results showed the conventional monetary transmission has continuity to inflation starting while monenter sharia showed no continuity of sharia variables leading to inflation , sharia is only continuous variables among these variables.Keywords : Inflation, Conventional Monetary Transmission, Sharia Monetary Transmission, VECM, Causality Test.